2003
DOI: 10.1002/ijc.11404
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of the androgen receptor by a point mutation in the hinge region: A new mechanism for androgen‐independent growth in prostate cancer

Abstract: Androgen receptor (AR) mutations that modify both the ligand binding and the transactivation capacities of the AR represent one of the mechanisms involved in the transition of prostate cancer (PCa) from androgen-dependent to androgen-independent growth. We use a yeast-based functional assay to detect and analyze mutant ARs in PCa. We report the detection of 2 different mutant ARs within the same metastatic tumour sample harvested in a patient with advanced PCa who had escaped androgen deprivation. Concomitantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 11 publications
(16 reference statements)
3
74
0
2
Order By: Relevance
“…The AR plays a key role in the development of prostate cancer and in resistance to hormone therapy (2, 3). Several point mutations in and around the hinge region have been identified in prostate cancer patients (6)(7)(8)(9)(10)(11). In our assays, both the R629Q and the K630T mutants (6, 7) have an increased potency (Fig.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The AR plays a key role in the development of prostate cancer and in resistance to hormone therapy (2, 3). Several point mutations in and around the hinge region have been identified in prostate cancer patients (6)(7)(8)(9)(10)(11). In our assays, both the R629Q and the K630T mutants (6, 7) have an increased potency (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Cancer Res 2007; 67: (9). May 1, 2007 We delineated the part of the hinge that inhibits the transcriptional activity of the full-length human AR to a highly basic motif between residue 629 and 636 (629-RKLKKLGN-636; Fig.…”
Section: Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…An important fraction of ARDCTD is nuclear and is able to bind DNA in the absence of ligand (28). Moreover, ARDCTD expression leads to constitutive activation of artificial androgen-responsive promoters in SDM (29)(30)(31)(32)…”
Section: Resultsmentioning
confidence: 99%
“…Structure function analysis of the AR showed that deletion of the LBD generates a constitutively active AR molecule (15). A subsequent study identified a nonsense mutation at Q640 that results in a truncated constitutively active AR in a tumor refractory to androgen ablation therapy (16). We and others previously reported that calpain cleaves the AR molecule to produce various LMW isoforms (17)(18)(19), including an ϳ80,000 C-terminally truncated AR.…”
mentioning
confidence: 97%